2018
DOI: 10.1002/csr.1516
|View full text |Cite
|
Sign up to set email alerts
|

The relative importance of employee green behavior for overall job performance ratings: A policy‐capturing study

Abstract: Organizational researchers and practitioners are increasingly interested in the topic of employee pro-environmental or 'green' behavior. In this study, we examine the relative importance of employee green behavior to overall job performance ratings compared with task performance, organizational citizenship behavior and counterproductive work behavior. We used an experimental policy-capturing design, which involves participants rating the job performance of several hypothetical employees who vary in their work … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 35 publications
1
21
0
Order By: Relevance
“…Tourism and hospitality industries are also facing the same environmental problems for example, energy, water and waste management etc. (Anser, Yousaf, Usman, & Yousaf, 2020; Becken & McLennan, 2017; Bohlmann, van den Bosch, & Zacher, 2018; Majid, Yasir, Yousaf, & Qudratullah, 2019) where managers can play a significant role in mitigating these concerns (Beaudoin, Cianci, Hannah, & Tsakumis, 2019). Existing studies in the relevant field reported that all members of the organizations should collectively make efforts to protect natural environment and contribute for the environmental performance (Osagie, Wesselink, Blok, Lans, & Mulder, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Tourism and hospitality industries are also facing the same environmental problems for example, energy, water and waste management etc. (Anser, Yousaf, Usman, & Yousaf, 2020; Becken & McLennan, 2017; Bohlmann, van den Bosch, & Zacher, 2018; Majid, Yasir, Yousaf, & Qudratullah, 2019) where managers can play a significant role in mitigating these concerns (Beaudoin, Cianci, Hannah, & Tsakumis, 2019). Existing studies in the relevant field reported that all members of the organizations should collectively make efforts to protect natural environment and contribute for the environmental performance (Osagie, Wesselink, Blok, Lans, & Mulder, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Tourism and hospitality industry, particularly small and medium sized hotels (SMSHs) are facing numerous environmental problems, for example, energy, water and waste management and so forth. (Becken & McLennan, 2017; Bohlmann, van den Bosch, & Zacher, 2018), where employees can play a significant role in mitigating these concerns (Hur, Moon, & Choi, 2019; Majid, Yasir, & Yasir, 2017). Despite the fact that many of research studies reported that all members of the organizations collectively make efforts to protect natural environment from degradation due to their business operations (Yu, Ramanathan, & Nath, 2017), however, in fact these are the employees who are the real actors in ensuring excellent EP in the organizations (Guerci, Longoni, & Luzzini, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Green training comprises a set of activities aimed at enhancing employees' environmental awareness, knowledge, and skills (Jabbour, ). Green performance and reward management involves setting green performance targets, using green indicators for performance evaluation (Bohlmann, van den Bosch, & Zacher, ), and recognizing contribution to environmental goals using financial and nonfinancial rewards (Jabbour, Jabbour, Govindan, Teixeira, & Freitas, ). Green involvement consists of encouraging employee participation in environment management via communication of clear green vision, creation of green learning climate, and development of green culture (Tang et al, ).…”
Section: Introductionmentioning
confidence: 99%